2011
DOI: 10.1111/j.1440-1797.2011.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Smaller low‐density lipoprotein size as a possible risk factor for the prevalence of coronary artery diseases in haemodialysis patients: Associations of cholesteryl ester transfer protein and the hepatic lipase gene polymorphism with low‐density lipoprotein size

Abstract: These suggest that a smaller LDL size, which is associated with higher levels of TG and CETP and the HL/CC genotype, may serve as a risk factor for CAD in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…The present study demonstrated that the plasma levels of TC, LDL-C, and lipoprotein(a) were significantly higher in the ACS and stable CHD groups compared to the control group. These blood lipid profiles have been confirmed with several independent lines of evidence (Kimura et al, 2011). The plasma level of HDL-C was lower in the ACS group than the stable CHD group, and was much lower than that of the control group.…”
Section: Discussionsupporting
confidence: 68%
“…The present study demonstrated that the plasma levels of TC, LDL-C, and lipoprotein(a) were significantly higher in the ACS and stable CHD groups compared to the control group. These blood lipid profiles have been confirmed with several independent lines of evidence (Kimura et al, 2011). The plasma level of HDL-C was lower in the ACS group than the stable CHD group, and was much lower than that of the control group.…”
Section: Discussionsupporting
confidence: 68%
“…Patients on hemodialysis form one of these important subpopulations because they are at a high risk for atherosclerosis. In this group, the link between sdLDL and coronary artery disease [2] and also survival [3] has recently been established.…”
Section: The Impact Of Different Ldl Subclass Profiles On Cardiovascumentioning
confidence: 99%
“…In the present study, a positive correlation was not observed between CETP and LDL-C or sd LDL-C at baseline. This may have been due to individual differences in sd LDL-C modifiers such as TG levels themselves and hepatic TG lipase activity according to gene polymorphisms [ 31 , 32 ]. In contrast, an independent positive association was observed between percentage changes in CETP and those in sd LDL-C because percentage changes in lipids represented the standardized effects of statins in each individual.…”
Section: Discussionmentioning
confidence: 99%